Chapter Professioni educative di ieri e di oggi: la "lezione delle cose" come itinerario di ricerca - Ferrari, Monica (Studi e saggi, 2019)
Starting from a reflection on the pedagogical analysis of professionalization processes from a diachronic perspective, the essay discusses a research perspective attentive to the "lesson of things" underlying the identification processes of individuals and social groups, by highlighting their training values for education professionals.